Energy storage-based control of multi-terminal DC grid to eliminate the fluctuations of renewable energy - Jiajun Nan; Wei Yao; Jinyu Wen (The Journal of Engineering, 2019)
DC grid technology is an effective approach to implement large-scale renewable energy integration and accommodation. However, because of randomness and volatility of renewable power generation, the stability and efficiency of the power grid with high penetration integration will be weakened. This study proposes an energy storage-based control for the multi-terminal DC grid, and a way of integration in photovoltaic stations and wind power generators. The energy storage unit will be inputted into the multi-terminal DC grid to provide power support so as to eliminate the fluctuations of renewable energy and stabilise power flow of AC grids. Firstly, the four-terminal DC grid topology is established, which includes wind power generation, photovoltaic power generation and energy storage unit. Also, the corresponding system control strategy is designed. Then, by using the PSCAD/EMTDC platform, the equivalent simulation model of DC grid is built and the simulation studies are carried out under different conditions. Simulation results show that the proposed control strategy based on energy storage unit can eliminate the fluctuations of renewable power effectively.